A child with a long-standing, intensely itching subcutaneous nodule on a thigh: an uncommon (?) reaction to commonly used vaccines. (24th January 2013) - Bergfors, Elisabet; Lundmark, Katarzyna; Nyström Kronander, Ulla
Abstract : A 2-year-old girl presented with an intensely itching subcutaneous nodule on the front of a thigh. The nodule persisted for 10 months until it was excised. Subsequent investigation for malignancy and systemic disease showed no pathological findings. The diagnosis, persistent itching vaccination granuloma, was revealed by hazard almost 2 years after the onset of symptoms. Persistent itching subcutaneous nodules at the injection site for aluminium containing vaccines (mostly diphtheria-tetanus-pertussis combination vaccines for primary immunisation of infants) may appear with a long delay after the vaccination (months), cause prolonged itching (years) and are often associated with contact allergy to aluminium. The condition is poorly recognised in Health Care which may lead to prolonged symptoms and unnecessary investigations.